2019
DOI: 10.1016/j.aott.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of type 1 complex regional pain syndrome: Osteoblastoma of the talus

Abstract: We report a 14-year-old boy who presented with pain in the left foot and ankle for about 9 months. The clinical symptoms of the patient suggested complex regional pain syndrome (CRPS). The radiographs and magnetic resonance imaging studies ravealed a bone tumor in the talus, consistent with an osteoblastoma. The patient underwent operative treatment with curettage and grafting. The complaints of the patient completely resolved by 6 months after surgery, and there was no recurrence at the postoperative 23th mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…CRPS as a complication of cancer treatment Massard et al 2009, 10 Case report 4 Unilateral lower extremity Metastatic renal cancer CRPS from systemic treatment Complete resolution despite continuation of cancer treatment Perez de Amezaga et al 2022, 16 1 Neuroendocrine tumor with hepatic metastasis Pain improved with analgesic medication and discontinuation of cancer treatment Magnol et al 2019, 17 Metastatic renal cancer Complete resolution despite continuation of cancer treatment Meeks et al 2022, 18 Acute lymphoblastic leukemia Complete resolution after multimodal analgesic medication Chi et al 2016, 19 Endometrial cancer and Lynch syndrome CRPS from surgery for cancer Pain improved after spinal cord stimulation 3. CRPS impacting cancer diagnosis Beytemur et al 2019, 20 Case report 1 Unilateral lower extremity Osteoblastoma of talus CRPS was the presenting symptom of tumor Complete resolution after cancer treatment Ku et al 1996, 21 2 Unilateral upper extremity Breast cancer; 1 Lymphoma 2 CRPS was the first symptom of metastasis; 1 CRPS was the symptom of new malignancy 2 Improvement of hand and shoulder function after cancer treatment Soliz et al 2016, 22 1 Prostate cancer CRPS led to the diagnosis of widespread metastatic cancer ...…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRPS as a complication of cancer treatment Massard et al 2009, 10 Case report 4 Unilateral lower extremity Metastatic renal cancer CRPS from systemic treatment Complete resolution despite continuation of cancer treatment Perez de Amezaga et al 2022, 16 1 Neuroendocrine tumor with hepatic metastasis Pain improved with analgesic medication and discontinuation of cancer treatment Magnol et al 2019, 17 Metastatic renal cancer Complete resolution despite continuation of cancer treatment Meeks et al 2022, 18 Acute lymphoblastic leukemia Complete resolution after multimodal analgesic medication Chi et al 2016, 19 Endometrial cancer and Lynch syndrome CRPS from surgery for cancer Pain improved after spinal cord stimulation 3. CRPS impacting cancer diagnosis Beytemur et al 2019, 20 Case report 1 Unilateral lower extremity Osteoblastoma of talus CRPS was the presenting symptom of tumor Complete resolution after cancer treatment Ku et al 1996, 21 2 Unilateral upper extremity Breast cancer; 1 Lymphoma 2 CRPS was the first symptom of metastasis; 1 CRPS was the symptom of new malignancy 2 Improvement of hand and shoulder function after cancer treatment Soliz et al 2016, 22 1 Prostate cancer CRPS led to the diagnosis of widespread metastatic cancer ...…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…CRPS can lead to the diagnosis of cancer, relapse and/or metastatic disease. 20 , 21 Any tumor invading neural structures may potentially cause symptoms compatible with CRPS. Ku A et al 21 reported two cases of patients with a history of breast cancer and thyroid cancer in clinical remission who presented to their clinic with clinical upper extremity CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of reported cases of osteoblastoma arising in bones of hands and feet 7–27 is summarized in Table 1. A total of 21 relevant English articles were collected.…”
Section: Discussionmentioning
confidence: 99%
“…Due to absence of response to salicylates, talus osteoblastoma may be wrongly diagnosed as ankle sprain [ 3 ]. Beytemur et al presented a case of talar osteoblastoma which presented as type 1 complex regional pain syndrome [ 6 ]. However, our case patient presented with a nonspecific swelling of the ankle with inability to bear weight and multiple varicosities over lateral aspect of the leg with a history a claudication.…”
Section: Discussionmentioning
confidence: 99%